Устойчивость тонких гофрированных оболочек, лежащих на упругом основании, под действием неоднородного гидростатического давления - Никонова, Т. В.; Михасев, Г. И. (БНТУ, 2008)
The problem of stability of the thin-walled corrugated shell laying on the elastic foundation under action of non- uniform pressure is considered. The influence of the elastic foundation is taken into account as the additional pressure within the framework of Winkler's model. The rigid clamped conditions are considered at the edges of the shell. The obtained resolving equation with respect to a normal deflection enables to calculate the value of the critical pressure.